Rh-relaxin-2 attenuates oxidative stress and neuronal apoptosis via ERK-nNOS-NO pathway after germinal matrix hemorrhage in rats - Jun Liu; Yonghua Cai; Khalil ur Rahman; Qixiong Zhou; Guangjie Liu; Huibin Kang; Mingzhou Li; Shichao Zhang; Gang Wang; Wenfeng Feng; Xi’an Zhang; Guozhong Zhang; et al. (Fluids and Barriers of the CNS)
Abstract Oxidative stress and neuronal apoptosis could be an important factor leading to post-hemorrhagic consequences after germinal matrix hemorrhage (GMH). Previously study have indicated that relaxin 2 receptor activation initiates anti-oxidative stress and anti-apoptosis in ischemia-reperfusion injury. However, whether relaxin 2 activation can attenuate oxidative stress and neuronal apoptosis after GMH remains unknown. To investigate the beneficial effect of relaxin 2 on oxidative stress injury and neuronal apoptosis by GMH, a total of 150 rat pups were subjected to GMH by an intraparenchymal injection of bacterial collagenase. Recombinant human relaxin-2 (rh-relaxin-2) was administered intraperitoneally injections at 1 h and 13 h after GMH. Lenti-virus with sgRXFP1 and sgCtrl was administered intracerebroventricular (i.c.v.) on the left side of the brain to inhibit the RXFP1 at 2d prior to GMH induction, and LY321499, ERK inhibitor, was administered by i.c.v. injection at 1 h on the left side of the brain prior to GMH induction, respectively. Co-immunoprecipitation, immunofluorescence, TUNEL, Fluoro-Jade C, DHE staining, western blot, Nitrix Oxide (NO) quantification and side effect experiments were performed to evaluate post-GMH. We found endogenous relaxin-2 interacts with RXFP1 and both protein colocalized in neurons on the first day after GMH. Additionally, RXFP1 activation with rh-relaxin-2 significantly inhibited oxidative stress and neuronal apoptosis in GMH + rh-relaxin-2 group compared with GMH + vehicle group. Moreover, rh-relaxin-2 treatment significantly inhibited the phosphorylation of ERK and nNOS, as well as upregulated expression of Bcl2 and NO and downregulated expression of Bax and Romo 1. The beneficial effects of rh-relaxin-2 were reversed by i.c.v. injection of lenti-virus with sgRXFP1 and LY321499, respectively. Furthermore, the side effect experiment showed rh-relaxin-2 did not affect neurological behavior and the function of liver and kidney. In conclusion, our finding showed that rh-relaxin-2 attenuated oxidative stress and neuronal apoptosis after GMH through RXFP1-ERK-nNOS-NO signaling pathway.